Do information contagion and business model similarities explain bank credit risk commonalities? - Dieter Wang; Iman van Lelyveld; Julia Schaumburg (Tinbergen Institute, 2018)
This paper revisits the credit spread puzzle in bank CDS spreads from the perspective of information contagion. The puzzle, first detected in corporate bonds, consists of two stylized facts: Structural determinants of credit risk not only have low explanatory power but also fail to capture common factors in the residuals (Collin-Dufresne et al., 2001). For the case of banks, we hypothesize that the puzzle exists because of omitted network effects. We therefore extend the structural models to account for information spillovers based on bank business model similarities. To capture this channel, we propose and construct a new intuitive measure for portfolio overlap using the complete asset holdings of the largest banks in the Eurozone. Incorporating the network information into the structural model for bank credit spreads increases explanatory power and removes a systemic common factor as well as a North-South common factor from the residuals. Furthermore, neglecting the network likely overstates the importance of structural determinants.
Keywords: G01; G21; C32; C33; C38; 330; Information contagion; credit spread puzzle; bank business model similarities; portfolio overlap measure; dynamic network effects model